Effect of differences in parenteral nutrition policies on preterm macronutrient intake: a telephone survey of all UK level 3 neonatal services. (24th May 2012) - Paize, F; Mahaveer, A; Morgan, C
Abstract : Background: A recent UK national audit revealed large variations in parenteral nutrition (PN) administration in a subgroup of neonatal patients1 . The factors involved included timeliness, nutritional adequacy and metabolic complications. It was not clear how much of this variation was due to differences in PN policy or whether very preterm infants (the most PN dependent) were more at risk. Aim: To estimate macronutrient intakes in very preterm infants resulting from local PN policy implementation in all level 3 UK neonatal services. Methods: A telephone survey using a structured questionnaire was performed Aug-Nov 2011. This recorded all factors affecting early PN supply and administration utilising information from the local PN guideline (infants <29 weeks gestation when applicable), neonatal pharmacists and neonatologists. This allowed protein, lipid and glucose intakes to be estimated. Local protocols for PN "intolerance" (that may affect macronutrient intake) including hyperglycaemia/hypertriglyceridaemia were also recorded. Results: All 60 UK level 3 (or equivalent) neonatal services provided data. Neonatal PN prescription/supply was wholly individualised (10%), individualised hybridised with standardised (56%), customised standardised (17%) or wholly standardised (17%). In only 2/60 units did local guidelines aim to introduce PN immediately after birth with 18/60 delaying >24 hours (6/60 due PN supply arrangements). This impacted on estimated early protein intake in particular (table 1 ). Estimated protein intakes were <1.5 g/kg/first 48 hours in 34 (57%) units and the routine daily maximum protein was below the minimum ESPGHAN recommendations in 13 (22%) units (table 1 ). Hyperglycaemia management protocols involved routine (68%) versus rare/never (32%) insulin treatment and routine (48%) versus rare/never (52%) reduction in glucose intake. Hypertriglyceridaemia (leading to intravenous lipid reduction) was monitored in 35 (58%) units. Conclusion: There is wide variation between UK level 3 neonatal services in the estimated macronutrient intake some of which results from local organisation of PN provision. There are opposing PN policy differences on the early introduction of protein, insulin-treated hyperglycaemia and triglyceride monitoring.